2010
DOI: 10.1021/jp108675b
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of Terpenoid Plant Extracts in Lipid Bilayers Investigated by Molecular Dynamics Simulations

Abstract: The plant Perilla frutescens is widely employed in Asian medicine. The active components of Perilla include cyclic terpenes, which have a diverse range of antimicrobial, anticancer, sedative, and anti-inflammatory properties, hinting at a membrane-mediated mechanism of action. We have used molecular dynamics (MD) simulations and isothermal titration calorimetry (ITC) to investigate the interaction of four terpenes with model lipid bilayers. The ITC and MD data are mostly in accordance. The terpenes partition i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 48 publications
(69 reference statements)
2
45
0
Order By: Relevance
“…POPC is a lipid well known model lipid used to model membranes both in simulations and in experiments in a large variety of systems, ranging from protein-membrane interactions such as ion-channel (19) and ion-pump simulations (4, 20 -22) to drug-binding assays (23). A POPC membrane is in the fluid phase at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…POPC is a lipid well known model lipid used to model membranes both in simulations and in experiments in a large variety of systems, ranging from protein-membrane interactions such as ion-channel (19) and ion-pump simulations (4, 20 -22) to drug-binding assays (23). A POPC membrane is in the fluid phase at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The MDS study demonstrated that different terpenes were able to partition into the model membranes with different association times, and these simulations were then correlated with experimental interaction data from ITC. 65 The ITC data showed that the membrane partitioning by some terpenes was enthalpically driven, whereas others were driven by entropy.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%
“…It can be seen that all the simulations identify the location of the molecule inside the bilayer regardless of the force field and lipid type. In some cases, more than one location was found to be stable, as for instance Limonene, Perillyl alcohol, Perillaldehyde, Perillic acid (Witzke et al 2010), and Diploptene and Bacteriohopanetetrol (Poger and Mark 2013), which are partitioned in the bilayer changing from one location to another. Other molecules, like Fusidic acid (Falck et al 2006), uncharged Lidocain (Högberg et al 2007) and Emodin (this work), prefer the head-tail interface near the ester or glycerol groups of the lipid.…”
Section: Discussionmentioning
confidence: 99%
“…There are several molecular features that govern the behavior of a drug in cell membranes such as size, shape, solubility, hydrophilicity, lipophilicity, and pK a , among others. Previously, many authors have reported studies of the interaction of drugs and membrane models with experimental technics (Nunes et al 2011;Lucio et al 2009;Fuchs et al 1990) and molecular dynamic (MD) simulations (Robinson et al 1995;Gabdouline et al 1996;Smondyrev andBerkowitz 1999, 2001;Hofsäß et al 2003;Pereira et al 2004;Falck et al 2006;Högberg et al 2007;Seddon et al 2009;Sirk et al 2009;Boggara and Krishnamoorti 2010;Witzke et al 2010;Orsi andEssex 2010, Koukoulitsa et al 2011;Nitschke et al 2012;Poger and Mark 2013;Loverde 2014;Jalili and Saeedi 2016). In particular, studies based on drug partitioning in lipid bilayers and the thermodynamics of drug/lipid interaction have great importance in understanding the reaction mechanisms of antitumor drugs and to design new cell membrane-targeted drugs (Boggara and Krishnamoorti 2010;Jendrossek and Handrick 2003;Goldstein et al 2011;Choi et al 2013).…”
Section: Introductionmentioning
confidence: 99%